THE EFFECTIVENESS OF USING ISPRING SUITE MEDIA TO TEACH SIMPLE PRESENT AND SIMPLE PAST ON 10TH GRADERS OF SMAN 1 REJOTANGAN - Fitrianto, Mochamad Arif; Septiana, Ayu Rizki (Cendikia: Jurnal Pendidikan dan Pengajaran, 2024)
Learning using technology nowadays has many benefits and advantages, but as a teacher you also have to know about the technology that has developed. Good teaching media is teaching media that becomes a bridge or link between teachers and students, besides that it can increase students' interest in learning. Teachers are also required to innovate in teaching using technology, because technology is diverse and has its own benefits, therefore teachers have a responsibility, apart from teaching material in class, to also learn about technology. In this research, researchers used Ispring suite 10 media which was created in the form of an application for learning in class XA at ​​SMAN 1 Rejotangan. This research used quantitavive research and pre-experiment type because take and class. Instrument research used worksheet with 20 multiple choice question and used expert validation. The research results showed significance as evidenced by the increase in students' average scores. The result of the finding showed that the mean score of pretest 75.69 to the mean posttest data of 85.14.